PENGARUH MODEL KOOPERATIF TIPE TSTS TERHADAP KETERAMPILAN MENULIS TEKS CERITA ULANG BIOGRAFI SISWA KELAS XI SMAN 1 PADANG - Adila, Mery; Ratna, Ellya; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ This research is aimed to explain the influence cooperative model type TSTS concerning re-biographical story writing skills of student class XI SMA Negeri 1 Padang. The research method of this study is experiment method with quasi experiment. The results of this study thre was significant influence cooperative model type TSTS concerning re-biographical story text writing skills of student class XI SMA Negeri 1 Padang at significant level 95% with degrees of freedom (dk) = n-1, namely tarithmetic > ttable (14,04 > 1,67). Ho was rejected and H1 was accepted because the results of the hypothesis test prove that value of tarithmetic was greater than ttable.Â Kata Kunci: pengaruh, kooperatif, TSTS, teks cerita ulang biografi